Managing The Interaction of Stakeholders In Ensuring Sustainable Development of Territories - (:unkn) unknown (Kharkiv : LTD “Typography Madrid”, 2022)
In the monograph, within the framework of the research work “Managing contradictions of interests of stakeholders in ensuring sustainable development of territories”, the authors present new results that relate to extremely urgent issues of reducing gaps in interests of stakeholders in the system of sustainable development of territories. The monograph is structured in three areas, which deal with highlighting the essence of the problem. The main results of the study relate to the following aspects of interaction of stakeholders in ensuring sustainable development of territories: the capital of stakeholders in the system of socio-economic development; the results of a survey of stakeholders of the corporate sector on the impact of European integration on sustainable territorial development; inclusive and sustainable growth; the impact of innovation on the development of social infrastructure of territories; key provisions of state regulation of infrastructure development in united territorial communities; budget resources as a factor of ensuring financial independence and development of the region; the stakeholder approach to the security of territorial business processes; the role of the stakeholder approach in ensuring sustainable social development of rural areas. The research is fundamental, based on a broad analysis of materials and sources, and contains modern, original ideas. The publication will be useful for scientists, teachers, public administration specialists, local authorities, non-governmental organizations, economists and individuals interested in coordinating the interests of stakeholders in ensuring sustainable development of territories.
Keywords: Stakeholders; Sustainable Development; Development of Territories